GAGASAN PENGATURAN KEBEBASAN MENYAMPAIKAN PENDAPAT DI MEDIA SOSIAL DALAM PERSPEKTIF HAK ASASI MANUSIA - Wan Hilfiana; Mexsasai Indra; Evi Deliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Freedom of expression is an important element in democracy as well as public participation in exercising their rights effectively both in terms of participation in making a public policy. Freedom of expression has several functions. This is a form of human rights implementation. Given the right to express opinions to the public, it means that one of the human rights has been recognized, guaranteed, and fulfilled.This study uses a typology of normative legal research or what is also called doctrinal legal research, which deals more specifically with legal principles. In this research, the writer uses descriptive research characteristic, because the writer describes the Arrangement of Freedom of Expressing Opinions on Social Media in a Human Rights Perspective.The result of the research conducted by the author is that the Government wants to revise the laws and regulations regarding Information Technology and Electronics, where there are weaknesses in the article that lead to multiple interpretations. In making revisions, it should pay attention to conformity with the relevant laws and regulations, in order to create a relevance between the laws and regulations and not contradict each other and there is a need for legal reform of the ITE Law and restructuring aimed at realizing consistent and sustainable legal protection in ensuring freedom of expression.Keywords: Arrangement- Freedom of Opinion- Social Media- Human Rights